2014
DOI: 10.1097/mib.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Discontinuation of TNFα-blocking Therapy in Patients with Inflammatory Bowel Disease in Deep Remission

Abstract: After cessation of TNFα-blocking therapy in patients with IBD in deep remission, up to 67% remained in clinical remission during the 12-month follow-up. Importantly, 85% of these patients sustained endoscopic remission. The response to restart of TNFα antagonists was effective and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 30 publications
5
51
0
1
Order By: Relevance
“…All achieved clinical remission within 14 weeks. This is consistent with other studies, which reported 93-96 % remission rates in CD patients and a 71 % remission rate in UC patients within 14 weeks of infl iximab retreatment (13,20,24).…”
Section: Effectiveness Of Retreatmentsupporting
confidence: 82%
See 1 more Smart Citation
“…All achieved clinical remission within 14 weeks. This is consistent with other studies, which reported 93-96 % remission rates in CD patients and a 71 % remission rate in UC patients within 14 weeks of infl iximab retreatment (13,20,24).…”
Section: Effectiveness Of Retreatmentsupporting
confidence: 82%
“…These include three retrospective and six prospective studies (11)(12)(13)(19)(20)(21)(22)(23)(24). All nine studies included rather few patients (14 to 121), all but two included only infl iximab stoppers, and only three studies included UC patients.…”
Section: Relapse Rates In Other Studiesmentioning
confidence: 99%
“…The median time to relapse was between 4.8 and 16.4 months across the studies reporting this outcome. 38,47,49,53,55,[57][58][59][60][61] Five studies 39,57,[62][63][64] included patients withdrawn from therapy while in both clinical and endoscopic remission. Radiological healing as assessed by magnetic resonance imaging was also shown in one study.…”
Section: De-escalation Of Anti-tnf In CDmentioning
confidence: 99%
“…In the case of extensive small bowel disease and/or symptomatic perianal fistulas, longterm treatment with anti-TNF agents is indicated, because alternative medical therapies are limited. [96][97][98] Retreatment of patients that experience a relapse after cessation of IFX therapy is usually well tolerated and the success rate is high, ranging from 71% to 94% in different studies. [96][97][98] Nevertheless, for IFX it is known that patients have an increased risk of developing (severe) infusion reactions and delayed hypersensitivity during reintroduction with IFX.…”
Section: Discontinuation and Reintroduction Of Anti-tnf Treatmentmentioning
confidence: 99%
“…[96][97][98] Retreatment of patients that experience a relapse after cessation of IFX therapy is usually well tolerated and the success rate is high, ranging from 71% to 94% in different studies. [96][97][98] Nevertheless, for IFX it is known that patients have an increased risk of developing (severe) infusion reactions and delayed hypersensitivity during reintroduction with IFX. [18,99,100] Despite limited evidence, we do recommend to always restart IFX together with corticosteroids and a H1-receptor antagonist as pre-medication in order to reduce the chance of developing an acute infusion reaction.…”
Section: Discontinuation and Reintroduction Of Anti-tnf Treatmentmentioning
confidence: 99%